Production, Proximate Composition and Sensory Evaluation of Cereal- Legume Based Infant Food - Abubakar, F.; Zigla, A. (ARID ZONE JOURNAL OF ENGINEERING, TECHNOLOGY AND ENVIRONMENT, 2021)
In this study, a cereal-legume based infant food was formulated from millet, malted millet, cowpea, soybeans, and groundnut. The grains used were blended into four infant formulations of different ratios namely: Formulation 1 (70% millet + 30% soybean), Formulation 2 (65% millet 4- 30% soybean + 5% malt), Formulation 3 (70% millet + 20% cowpea + 10% groundnut) and Formulation 4 (65% millet 4- 20% cowpea + 10% groundnut + 5% malt). Standard methods of analysis were used to determine the moisture content, crude fat, crude protein, ash, pH, titrable acidity (TA), total sugar and bulk density contents for the different formulations; whereas the carbohydrate was computed by difference. Each of the samples from the formulations produced was cleaned, toasted, and milled together. The infant formulations were given to 120 mothers residing within Lake Chad Research Institute, Maiduguri and Usmanti area, which is close to Lake Chad Research Institute, Maiduguri. The prepared infant formulations were made into slurry with boiled water and given to the mothers in order to serve their children when slightly cooled. A 9-point hedonic scale was used in the sensory evaluation of the products. Results obtained showed that the moisture content ranged from 4.4 to 6.5%, ash from 1.5 to 1.9%, protein from 13.6 to 22.1%, carbohydrate from 68.6 to 75.5% and fat from 2.3 to 4.9%; whereas the pH and TA values ranged from 5.5 to 5.6, and 0.68 to 0.74, respectively, while the total brix sugar value ranged from 14.2 to 29.8. The results for sensory evaluation indicated that the cereal-legume based formulations were generally accepted by the mothers for their babies in all the parameters determined. The study indicated that Formulations 3 and 4 had the highest scores for overall acceptability.